Neoplasia Ablation in the Equine Oral Cavity Vestibule - Ferreira, Manoel Luiz; Alzamora Filho, Fernando; Gracie Mery, Raissa Barros; de Santana Santos, Jullie Souza; de Sousa Barros, Jonatas Rochael; Machado, Marina Cartagena; Alves da Silva, Marcus Vinicius; Cesar Silva, Paulo (Acta Scientiae Veterinariae, 2020)
Background: Oral squamous cell carcinoma is responsible for more than 90% of head and neck neoplasms in humans. Multiple factors are associated with the development of squamous cell carcinomas in humans and animals, such as prolonged exposure to ultraviolet light, lack of pigment in the epidermis, or sparse hair coverage. In horses, oral forms are rare and represent 7% of cases, but sarcoids are the main type of oral neoplasia. In the present case, due to the location and anatomical dimensions of the oral vestibule, it was necessary to adapt it to the natural tumor excision, a fact that aimed to describe this report. Case: One Arabian 2- year-old male horse, treated at the Veterinary Hospital of the Santa Cruz State University (UESC), with signs of severe mouth bleeding and halitosis. Clinical inspection of the face showed elevation in the masseter region and left mandible branch. Clinical examination of the oral cavity revealed soft tissue tumor extending from tooth 308 (PM-1, lower left) to 311 (M-3, lower left) and on the buccal surface of the left mandible branch. Radiographic examination revealed no invasion of bone tissue by the tumor. Biopsy material was collected. The histopathological report was of neoplastic cell proliferation, frequent mitoses, binucleate cells and extensive ulceration area associated with neutrophilic inflammatory infiltrate, indicative of squamous cell carcinoma. The animal was referred to the Surgical Sector who, after evaluation of the animal, opted for the ablation of the neoplasia. Pre-anesthesia performed with intravenous detomidine 30 µg/kg, anesthesia with regional mandibular nerve block with 20 mL of 2% lidocaine and maintenance with continuous infusion of detoxid 0.5 µg/kg/ min. Contention for the operative act in the quadrupedal position. The opening of the oral cavity through the Holborn ratchet opener. The beginning of the surgery was with the scalpel, which allowed the removal of approximately one third of the tumor. Due to the great difficulty of fully accessing the area, due to the location of the tumor in the vestibule of the mouth, as well as the presence of fibrosis and calcification, it was necessary to adapt a 15 cm lambotte rugina to allow manipulation and perfect access to the entire mass. tumor for its complete ablation. The synthesis was not performed due to the anatomy and extension of the bed where the tumor was located, which similarly favored drainage. The surgical specimen was treated and fixed in 10% formaldehyde and sent to the Pathology Department for histopathological diagnosis. Immediate postoperative medication consisted of intravenous tranexamic acid administration 5 mg/kg; flunixin megluminate 2.2 mg/kg intramuscularly for three days; intravenous metronidazole 15 mg/kg for ten days and a diet of easily digestible pasture. Discussion: Exeresis of surrounding lymph nodes is indicated, associated with treatment of electrochemotherapy, as oncologists have obtained excellent prognosis and survival of dogs and cats with oral neoplasms. This therapeutic modality may allow the treatment of cancers in horses, since the electric pulse increases the cytotoxicity of chemotherapeutic drugs. Tumors of the oral cavity of horses, due to the signs and symptoms manifested, must be diagnosed and treated urgently, clinically and surgically, due to the evolutionary characteristics of these diseases.